ANALYSIS OF THE IMPACT OF FAMILY OFFICE POLICY ON THE INCREASE OR DECREASE OF SOCIAL INEQUALITY IN INDONESIA: LITERATURE STUDY - BERNADETH TONGLY; VIRGILIA GLORIA VICA; VISHNU GAMA PUTRA JARANGGA (Ikatan Dosen Katolik Indonesia, 2026)
Family offices have been implemented in various countries as a means to manage family wealth more effectively, providing specific benefits such as tax incentives, investment policies licensing facilitation, and government support. This article evaluates the impact of family office policies on social inequality through a comprehensive literature review by analyzing academic sources, policy reports, and government documents from various jurisdictions including the United States, Singapore, and Switzerland. Although family office policies have shown effectiveness in developing countries, there are concerns regarding their relevance in developing countries such as Indonesia. The main question is whether the urgency of implementing family office policies truly exists in developing countries, or whether these policies merely benefit the super-rich, ultimately exacerbating social inequality. The literature review indicates that family office policies have a dual impact on social inequality. On one hand, family offices can exacerbate inequality by concentrating wealth in the hands of wealthy families, minimizing wealth redistribution and economic access for middle and lower economic groups. On the other hand, there is evidence that family offices also create new economic opportunities through direct investments that can reduce income disparities in certain areas. This study concludes that the impact of family office policies on social inequality depends heavily on the design and implementation of these policies. Therefore, a more holistic approach is needed in formulating family office policies to ensure that economic benefits are more widely distributed and social inequality is minimized.